Pandemic changes in work, rest, physical activity and diet versus nutritional status of respondents - Jawień, Wiktoria; Kania Barys, Barbara; Kądziołka, Anna; Jurkiewicz, Beata (Journal of Education, Health and Sport, 2022)
The aim of the study was to determine how the COVID-19 pandemic affected the nutritional status of the respondents through changes in work mode, physical activity and diet among residents of the Tarnów region. Material and methods. The study was conducted using the diagnostic survey method, and the tool was the author’s questionnaire. The study was conducted in January-February 2022, using the Google Forms platform. In total, data were collected from 414 people. The questionnaires were filled out mostly by women (67.9% vs. 32.1%). The average age of respondents was 31.9 years (±13.52). Results. Those who worked remotely and in hybrid mode had the highest percentages declaring an increase in food intake during the COVID-19 pandemic (65.0% and 59.7%, respectively). The highest percentages of those who indicated a deterioration in the quality of their food intake were those who worked remotely (60.0%) and hybrid job (45.5%), while those who did not work were the group that most often among the others indicated an improvement in the quality of their food (23.4%). Respondents with remote and hybrid jobs were the most likely to report a reduction in their activity level (72.5% and 58.4%, respectively). Considering the BMI of those surveyed before the COVID-19 pandemic and now, there is an apparent decrease in the percentage of those with a normal BMI in favor of overweight and obesity. Conclusions. During the COVID-19 pandemic period, the percentages of overweight and obese people increased. People working remotely and in hybrid mode not only increased the amount of food they consumed, but also began to consume lower-quality products, as well as more often reporting reduced levels of physical activity.